Imbalance of helper T cell type 1, helper T cell type 2 and associated cytokines in patients with systemic lupus erythematosus: A meta-analysis - Xiang, Shate; Zhang, Jingjing; Zhang, Mengge; Qian, Suhai; Wang, Rongyun; Wang, Yao; Xiang, Yingshi; Ding, Xinghong (Frontiers in Pharmacology, 2022)
Objective: Th1 and Th2 cells and their associated cytokines function in the pathogenesis of systemic lupus erythematosus (SLE), but their exact roles are uncertain. We performed a meta-analysis to examine the relationship of these cells and cytokines with SLE. Methods: Multiple databases were searched to identify publications that reported the percentages of Th1 and Th2 cells and their associated cytokines in SLE patients and healthy controls (HCs). Meta-analysis was performed using Stata MP version 16. Results: SLE patients had a lower percentage of Th1 cells, a higher percentage of Th2 cells, and higher levels of Th1- and Th2-associated cytokines than HCs. SLE treatments normalized some but not all of these indicators. For studies in which the proportion of females was less than 94%, the percentage of Th2 cells and the level of IL-10 were higher in patients than HCs. SLE patients who had abnormal kidney function and were younger than 30 years old had a higher proportion of Th1 cells than HCs. SLE patients more than 30 years old had a higher level of IL-6 than HCs. Conclusion: Medications appeared to restore the balance of Th1 cells and other disease indicators in patients with SLE. Gender and age affected the levels of Th1 and Th2 cells, and the abnormally elevated levels of Th2 cells appear to be more pronounced in older patients and males.